Pengaruh Indikator Ekonomi Hijau terhadap Kualitas Hidup Manusia di Indonesia Tahun 2021 - Septian, Dicky Aulia; Siburian, Lastri Ramadani; Hakim, Rafi Ariq; Kartiasih, Fitri (Seminar Nasional Official Statistics, 2025)
Economic development has serious implications for environmental sustainability, affecting the well-being of people in a country. This problem requires initiatives to implement green economy policies with the principle of involving economic development in line with the efficient use of natural resources so as to achieve a good quality of human life. This study aims to analyze the effect of green economy implementation on the quality of human life with descriptive and inferential analysis methods. This research uses multiple linear regression analysis and K-Means Clustering. With the K-Means Clustering method, three provincial clusters with the lowest to highest average Human Development Index (HDI) were obtained. The results showed that the area of forest land cover and poverty line significantly reduced HDI. However, Gross Regional Domestic Product per Capita at Current Prices significantly increases HDI. This study highlights the crucial role of green economy in shaping development pathways that are not only focused on economic growth, but also on maintaining ecological balance and improving human quality of life.